Survival Benefit for Individuals With Constitutional Mismatch Repair Deficiency Undergoing Surveillance. Issue 25 (1st September 2021) - Durno, Carol; Ercan, Ayse Bahar; Bianchi, Vanessa; Edwards, Melissa; Aronson, Melyssa; Galati, Melissa; Atenafu, Eshetu G.; Abebe-Campino, Gadi; Al-Battashi, Abeer; Alharbi, Musa; Azad, Vahid Fallah; Baris, Hagit N.; et al.
Abstract : PURPOSE: Constitutional mismatch repair deficiency syndrome (CMMRD) is a lethal cancer predisposition syndrome characterized by early-onset synchronous and metachronous multiorgan tumors. We designed a surveillance protocol for early tumor detection in these individuals. PATIENTS AND METHODS: Data were collected from patients with confirmed CMMRD who were registered in the International Replication Repair Deficiency Consortium. Tumor spectrum, efficacy of the surveillance protocol, and malignant transformation of low-grade lesions were examined for the entire cohort. Survival outcomes were analyzed for patients followed prospectively from the time of surveillance implementation. RESULTS: A total of 193 malignant tumors in 110 patients were identified. Median age of first cancer diagnosis was 9.2 years (range: 1.7-39.5 years). For patients undergoing surveillance, all GI and other solid tumors, and 75% of brain cancers were detected asymptomatically. By contrast, only 16% of hematologic malignancies were detected asymptomatically ( P < .001). Eighty-nine patients were followed prospectively and used for survival analysis. Five-year overall survival (OS) was 90% (95% CI, 78.6 to 100) and 50% (95% CI, 39.2 to 63.7) when cancer was detected asymptomatically and symptomatically, respectively ( P = .001). Patient outcome measured by adherence to the surveillance protocol revealed 4-year OS of 79% (95% CI, 54.8 to 90.9) for patients undergoing full surveillance, 55% (95% CI, 28.5 to 74.5) for partial surveillance, and 15% (95% CI, 5.2 to 28.8) for those not under surveillance ( P < .0001). Of the 64 low-grade tumors detected, the cumulative likelihood of transformation from low-to high-grade was 81% for GI cancers within 8 years and 100% for gliomas in 6 years. CONCLUSION: Surveillance and early cancer detection are associated with improved OS for individuals with CMMRD.